2021
DOI: 10.3390/agriculture11080724
|View full text |Cite
|
Sign up to set email alerts
|

MODIS NDVI Multi-Temporal Analysis Confirms Farmer Perceptions on Seasonality Variations Affecting Apple Orchards in Kinnaur, Himachal Pradesh

Abstract: Apple cultivation in the Kinnaur district of the northern Indian State of Himachal Pradesh faces challenges from climatic changes and developmental activities. Farmers in the neighboring districts have already faced a major loss of livelihood due to seasonal changes. Therefore, it is important to study the extent of seasonal variations in the apple growing locations of this region. This study makes that attempt by assessing seasonality variations during a 15-year period from 2004 to 2018 when maximum construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Similarly, a moderate correlation was found between soil moisture and wind speed. The apple growth condition was very nicely correlated with the normalized difference vegetation index, which similarly existed between snow index and rainfall 10 …”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, a moderate correlation was found between soil moisture and wind speed. The apple growth condition was very nicely correlated with the normalized difference vegetation index, which similarly existed between snow index and rainfall 10 …”
Section: Resultsmentioning
confidence: 80%
“…The installation of snow gauges at IMD-controlled weather stations is also critically needed to gather reliable data on the snowfall and other natural calamities information in the region and on the event-specific patterns of snowfall. This will allow policymakers and decision-makers to make informed decisions regarding weather variations 10 . Low suitability areas may be allotted the alternative horticulture crops and best agronomic practices management for sustainable agricultural planning 60 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite sensors have been widely used for observing the phenological stages of plants. Gupta et al [22] showed that apple growth was highly correlated with the Normalized Difference Snow Index (NDSI). Aragones et al [23] proved that pine species could be classified using phenology-derived classes using the Normalised Difference Vegetation Index (NDVI) in Mediterranean forest.…”
Section: Introductionmentioning
confidence: 99%